CHEER National Study of Chronic Rhinosinusitis Practice Patterns: Disease Comorbidities and Factors Associated with Surgery. (April 2017) - Chapurin, Nikita; Pynnonen, Melissa A.; Roberts, Rhonda; Schulz, Kristine; Shin, Jennifer J.; Witsell, David L.; Parham, Kourosh; Langman, Alan; Carpenter, David; Vambutas, Andrea; Nguyen-Huynh, Anh; Wolfley, Anne; et al.
Objectives: (1) Describe national patterns of chronic rhinosinusitis (CRS) care across academic and community practices. (2) Determine the prevalence of comorbid disorders in CRS patients, including nasal polyposis, allergic rhinitis, asthma, and cystic fibrosis. (3) Identify demographic, clinical, and practice type factors associated with endoscopic sinus surgery (ESS). Study Design: Multisite cross-sectional study. Setting: Otolaryngology's national research network CHEER (Creating Healthcare Excellence through Education and Research). Subjects and Methods: A total of 17, 828 adult patients with CRS were identified, of which 10, 434 were seen at community practices (59%, n = 8 sites) and 7394 at academic practices (41%, n = 10 sites). Multivariate logistic regression was used to evaluate the association between demographic, practice type, and clinical factors and the odds of a patient undergoing ESS. Results: The average age was 50.4 years; 59.5% of patients were female; and 88.3% were Caucasian. The prevalence of comorbid diseases was as follows: allergic rhinitis (35.1%), nasal polyposis (13.3%), asthma (4.4%), and cystic fibrosis (0.2%). In addition, 24.8% of patients at academic centers underwent ESS, as compared with 12.3% at community sites. In multivariate analyses, nasal polyposis (odds ratio [OR], 4.28), cystic fibrosis (OR, 2.42), and academic site type (OR, 1.86) were associated with ESS ( P < .001), while adjusting for other factors. Conclusions: We describe practice patterns of CRS care, as well as demographic and clinical factors associated with ESS. This is the first study of practice patterns in CRS utilizing the CHEER network and may be used to guide future research.